Vowel Formant Profiles and Image Schemata and Auditory Display - Roddy, Stephen; Furlong, Dermot (My University, 2018)
This paper presents two evaluations intended to examine if listeners are more likely to associate certain vowel formant profiles with specific data types in an auditory display context. The data types and sounds chosen to reflect those data types are informed by findings from the field of cognitive science. The results of the evaluations suggest that to a limited degree, listeners associate certain vowel formant profiles with strength, largeness of size, darkness and tension. The results further suggest that the amount of noise present in the vocal gesture effects the listeners perception of the tension represented in the sound. These results have implications for the field of auditory display.
Proceedings of the 32nd International BCS Human Computer Interaction Conference (HCI 2018) (HCI)
International BCS Human Computer Interaction Conference (HCI 2018)
Keywords: Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities; Inclusive Society; Smart & Sustainable Planet; Telecommunications; Auditory Display; Human-Computer Interaction; SPEECH PROSODY; Sonification; Accessibility; Home and community living